Investigating the controls on fault rock distribution in normal faulted shallow burial limestones, Malta, and the implications for fluid flow. (September 2018) - Cooke, Andy P.; Fisher, Quentin J.; Michie, Emma A.H.; Yielding, Graham
Abstract: The spatial distribution and fabric of carbonate fault rocks observed at outcrop are often highly heterogeneous. Therefore, petrophysical properties of fault rock samples may not be representative of the overall sealing capacity of the fault zone. By quantifying the fault rock distributions (i.e. fault rock thickness and fault rock continuity) of several fault zones in Malta, juxtaposing shallow burial limestones, this work investigates the relationship between fault zone architecture, deformation mechanisms, and fault rock distribution. Results from microstructural analyses indicate that high porosity (>15%) grain-dominated limestones deform via grain scale deformation, as opposed to fracture-derived cataclasites often observed in tight carbonates. Low porosity (<15%) grain-dominated limestones and high porosity micrite-dominated limestones deform in a more distributed manner, through extensional fracturing and brecciation. Fault rock continuity estimates suggest displacements of 50–200 m are required to form a continuous low-permeability cataclasite veneer in the studied sequence. However, greater displacements may be required when a distributed damage zone is present, in which strain is accommodated over multiple slip surfaces. This work highlights the heterogeneity in the distribution and fabric of carbonate fault rocks within fault zones hosting tens of meters displacement, and the importance of considering fault rock thickness and continuity when estimating the sealing capacity of a carbonate-hosted fault zone. Highlights: High porosity grain-dominated limestones deform via grain scale cataclasis. A distributed damage zone (DDZ) hosts multiple slip surfaces accommodating strain. A DDZ is characterized by discontinuous fault rock distributions. DDZ occur within low porosity limestones or in regions of structural complexity. Cataclasite in high porosity limestones is discontinuous at <50 m displacement.